Wandering Through the Desert with Multiple Sclerosis: How Outdoor Life Recalibrates Body Awareness and Self-Identity - Joeri Calsius; Minne Van Den Noortgate; Gert Roncada; Paul Van Asch; Marie D’hooghe (Journal of Interdisciplinary Sciences)
People with multiple sclerosis benefit from exercise, however, they commonly lead a more sedentary lifestyle. Therefore, they may lack the positive effects of activity on body awareness and selfidentity. This study explores changes in body awareness and identity in people with multiple sclerosis after a unique hiking expedition through the Jordan desert in the spring of 2014. A qualitative study design was applied, the interpretative phenomenological analysis method was used in a focus group with all nine participants of the expedition. Three main themes and six subthemes were identified to explore this study on a thematic basis. The first main theme ‘Peers and society’ focused on group dynamics and social stigma. The second theme, the ‘Lived body’ discussed bodily experiences and selfidentity. In the third theme, ‘Therapeutic effects’ of the journey and their implementation into daily life were explored. The findings suggest that participating in this unique hiking project had a powerful effect on the lived body experience of the participants. Experiencing outdoor life brought them back to basics, changed their bodily attunement and empowered their self-belief and social resilience. Several participants described this experience as an awakening in dealing with multiple sclerosis